Bina Desa Untuk Kesehatan Ibu Hamil: Pemanfaatan Gym Ball dan Rebozo - Hurin'in, Nur Maziyah; Febbyanca, Chelsea Anandita; Rosyita, Khoirur (Health Care : Journal of Community Service, 2025)
Lower back pain is a common complaint often experienced by pregnant women, especially in the third trimester, which can reduce quality of life and interfere with daily activities. Based on an initial survey in Tasikharjo Village, Tuban, it was found that 7 out of 10 pregnant women in the third trimester complained of back pain but had limited knowledge about safe non-pharmacological treatment. This community service activity aims to provide education and assistance regarding the use of Gym ball and Rebozo as a method to reduce back pain. This activity was carried out at Café Boum Tasikharjo Village and was attended by 25 pregnant women. The methods used were education, demonstration, and direct practice by participants. Evaluation was carried out through pre-tests and post-tests to measure increased knowledge as well as observation and feedback during the practice session. The results of the activity showed a significant increase in participant knowledge. Participants showed high enthusiasm, especially in the use of Gym balls which was felt to be more practical and effective to do independently. This activity succeeded in increasing the knowledge and skills of pregnant women in managing back pain independently, so that it is expected to increase comfort during pregnancy.